Missing Linker Defects in Heterometallic (Zn/Cd)-MOF-5: A First-Principles Study of Structural Properties and Gas Interaction - Fajar Inggit Pambudi; Eko Sri Kunarti; Robby Noor Cahyono; Nabila Nur Agusti (Masyarakat Katalis Indonesia - Indonesian Catalyst Society (MKICS), 2025)
The defect structures in multicomponent metal-organic frameworks (MOFs), specifically mixed-metal (Zn/Cd)-MOF-5, were investigated by examining the removal of a benzenedicarboxylate (bdc2-) linker. The defect formation, induced by the reaction with water, was studied, and the reaction energy was calculated to be relatively low, ranging from 0.24 eV to 0.60 eV. The removal of a bdc2- linker is energetically favourable when it is initially coordinated to both Zn2+ and Cd2+ ions. The electronic properties of defective (Zn/Cd)-MOF-5 were analyzed in terms of bandgap energy and density of states profile. The removal of the bdc2- linker slightly reduced the bandgap energy and affected the electronic states of both carbon and oxygen atoms. To evaluate the impact of defects, interactions with various gas molecules, including H2O, CO2, CO, H2S, and NO2, were studied. The defective (Zn/Cd)-MOF-5 showed a strong preference for H2O molecules, while CO2 exhibited the lowest binding preference among the gases studied. Copyright © 2025 by Authors, Published by BCREC Publishing Group. This is an open access article under the CC BY-SA License (https://creativecommons.org/licenses/by-sa/4.0).